The Emergence of Tax Regulation in Kuait: The 1899-1950s Episteme - Fakhra, Mahmoud M.S.A. (Accounting Department,, 1996)
The main focus of this study is on the interrelation between the process of setting government tax and accounting regulations in Kuwait during the period 1899-1950S and the environment which these regulations operate. This concern is pursued from a historical and contextual perspective, focusing on two major components, firstly on two tax laws which addressed accounting issue, secondly on the environmental (social, economic, and political) developments of the period 1899-1950s. Â The accounting literature on the process of setting accounting standards will not be used to guile the structure and the procedural steps of the present study. This is maintained on the ground that studies in the accounting literature are based on environments and on regulatory systems didderent from that in Kuwait. This is based on Foucauldian approach utilized in this study. By pursuing the task outlined above the following conclusions are obtained. Firstly, the understanding of the accounting regulatory process requires the identification and delineation of the wider social context regardless of the type of the regulatory system and regardless of its economic is interrelated with unlimited associated environmental (social, economic, and political) developments.